2012
DOI: 10.3390/en5030599
|View full text |Cite
|
Sign up to set email alerts
|

Using Submarine Heat Pumps for Efficient Gas Production from Seabed Hydrate Reservoirs

Abstract: This article reports our novel idea about the thermal stimulation of seabed hydrate reservoirs for the purpose of natural gas production. Our idea is to use submarine heat pumps, which are to be placed near the hydrate reservoir and work to recover thermal energy from the surrounding seawater and supply it into the reservoir. Although the heat pumps need an electricity supply from the sea surface level, they can provide thermal energy which is several times that of the consumed electricity in quantity. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In detail, a finite amount of heat input can effectively augment the rate of NGH dissociation. By contrast, if excessive and indiscriminate heat is input, the only a little facilitating effect on the NGH dissociation may be obtained due to the heating of sediments and gas–liquid phase in porous, and the massive and meaningless heat loss to the external environment, helping us understand the importance of the principle of “directional and quantitative heat supply” to reduce unnecessary heat loss. , A large number of experiments also have shown that the use of the in-situ heating method in HBS with high NGH saturation can achieve promising ξ and EER, and mutative scale optimization of the heating rate, rather than a constant heating rate, may be the best strategy for hydrate exploitation with the dynamic change of the temperature and three-phase saturation in the course of NGH dissociation . Besides, some regularity of the influence of the initial free water in HBS and the decomposed water from NGH, porosity, depth, and thickness of HBS and length of production wells on EER also needs to be studied when using the heat thermal stimulation method …”
Section: Methods Of Gas Recovery From Hbsmentioning
confidence: 99%
“…In detail, a finite amount of heat input can effectively augment the rate of NGH dissociation. By contrast, if excessive and indiscriminate heat is input, the only a little facilitating effect on the NGH dissociation may be obtained due to the heating of sediments and gas–liquid phase in porous, and the massive and meaningless heat loss to the external environment, helping us understand the importance of the principle of “directional and quantitative heat supply” to reduce unnecessary heat loss. , A large number of experiments also have shown that the use of the in-situ heating method in HBS with high NGH saturation can achieve promising ξ and EER, and mutative scale optimization of the heating rate, rather than a constant heating rate, may be the best strategy for hydrate exploitation with the dynamic change of the temperature and three-phase saturation in the course of NGH dissociation . Besides, some regularity of the influence of the initial free water in HBS and the decomposed water from NGH, porosity, depth, and thickness of HBS and length of production wells on EER also needs to be studied when using the heat thermal stimulation method …”
Section: Methods Of Gas Recovery From Hbsmentioning
confidence: 99%
“…It is important to apply an effective heat source and to reduce loss in the heat generation process. Electrical heating (Callarotti, 2011;Minagawa et al, 2018), an application of heat pump to collect sea water temperature (Mori et al, 2012), geothermal energy (Japan Drilling Company, 2009), and backfilling of chemical heat sources (Xu et al, 2021) have been proposed. Among those techniques, Callarotti (2011) estimated EROI of the thermal stimulation with electric heating using analytical solutions and obtained as in the range of 4-5 without considering the efficiency of power generation.…”
Section: Heat Demand and Output By Gas Production Methods Production Techniques And Theoretical And Laboratory Evaluationmentioning
confidence: 99%
“…Mori et al [2] proposed using submarine heat pumps that have a distinct thermodynamic advantage over other thermal stimulation techniques for energy saving potential. Peigné et al [3] designed a system to heat a low-energy building by coupling a heat-recovery ventilation system with a three-fluid heat exchanger located on the chimney of a wood-pellet stove and their case study results showed that heat transfer rates can be predicted with a relative difference lower than 5%.…”
Section: Introductionmentioning
confidence: 99%